Visual tests predict dementia risk in Parkinson disease. Issue 1 (February 2020) - Leyland, Louise-Ann; Bremner, Fion D.; Mahmood, Ribeya; Hewitt, Sam; Durteste, Marion; Cartlidge, Molly R.E.; Lai, Michelle M.-M.; Miller, Luke E.; Saygin, Ayse P.; Keane, Pearse A.; Schrag, Anette E.; Weil, Rimona S.
Abstract : Objective: To assess the role of visual measures and retinal volume to predict the risk of Parkinson disease (PD) dementia. Methods: In this cohort study, we collected visual, cognitive, and motor data in people with PD. Participants underwent ophthalmic examination, retinal imaging using optical coherence tomography, and visual assessment including acuity and contrast sensitivity and high-level visuoperception measures of skew tolerance and biological motion. We assessed the risk of PD dementia using a recently described algorithm that combines age at onset, sex, depression, motor scores, and baseline cognition. Results: One hundred forty-six people were included in the study (112 with PD and 34 age-matched controls). The mean disease duration was 4.1 (±2·5) years. None of these participants had dementia. Higher risk of dementia was associated with poorer performance in visual measures (acuity: ρ = 0.29, p = 0.0024; contrast sensitivity: ρ = −0.37, p < 0.0001; skew tolerance: ρ = −0.25, p = 0.0073; and biological motion: ρ = −0.26, p = 0.0054). In addition, higher risk of PD dementia was associated with thinner retinal structure in layers containing dopaminergic cells, measured as ganglion cell layer (GCL) and inner plexiform layer (IPL) thinning (ρ = −0.29, p = 0.0021; ρ = −0.33, p = 0.00044). These relationships were not seen for the retinal nerve fiber layer that does not contain dopaminergic cells and were not seen in unaffected controls. Conclusion: Visual measures and retinal structure in dopaminergic layers were related to risk of PD dementia. Our findings suggest that visual measures and retinal GCL and IPL volumes may be useful to predict the risk of dementia in PD.